Cellular interactions in aspirin-exacerbated respiratory disease. Issue 1 (February 2021) - Badrani, Jana H.; Doherty, Taylor A.
Abstract : Purpose of review: The purpose of this review is to summarize the complex cellular interactions of aspirin-exacerbated respiratory disease (AERD) and how these interactions promote pathogenic mechanisms of AERD. Recent findings: In addition to characteristic changes in eicosanoid levels, recent studies have identified increases in alarmin cytokines (IL-33, thymic stromal lymphopoietin) as well as activated innate lymphoid and plasma cell populations in samples from AERD patients. Summary: Patients with AERD typically demonstrate high levels of proinflammatory eicosanoids including cysteinyl leukotrienes (CysLTs) and prostaglandin D2 (PGD2 ) and hyporesponsiveness to prostaglandin E2 (PGE2 ). CysLTs are released by mast cells, eosinophils, and adherent platelets and promote epithelial release of IL-33, which activates mast cells and group 2 innate lymphoid cells (ILC2s) in concert with CysLTs. TSLP induces PGD2 release from mast cells which activates and recruits eosinophils, basophils, Th2 cells, and ILC2s via CRTH2. In turn, ILC2s and other cell types produce Th2 cytokines IL-4, IL-5, and IL-13 that, along with CysLTs and PGD2, promote bronchoconstriction, eosinophilic tissue inflammation, and mucus production.